KAWIN KONTRAK SEBAGAI INDIKATOR TRANSFORMASI BUDAYA HUKUM PERKAWINAN DI BALI - Praningsih, Cerry; Paramita, Dianing; Huda, Royan Miftahul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The practice of contractual marriages between Indonesian citizens (WNI) and foreign citizens (WNA) in Bali has increased significantly, especially along with the increasing foreign investment in the property sector. This phenomenon not only reflects the institution of marriage as a means to avoid legal restrictions, but also reflects the transformation of legal culture in Balinese society. Contractual marriages are often used as a tool to facilitate nominee agreements, where foreign citizens use the names of Indonesian citizens to obtain land rights that cannot legally be owned by foreigners. From a legal perspective, this practice creates a geography regarding the legitimacy of marriage relations, ownership of property, and legal protection for the parties. Meanwhile, from a socio-cultural perspective, this practice has the potential to erode customary values, land spirituality, and the social structure of Balinese society. This study aims to examine contractual marriages as one indicator of changes in the legal culture of marriage, by examining the interaction between customary norms, national law, and global economic interests. With a juridical-sociological approach, this study is expected to provide a deep understanding of the dynamics of law and culture in the context of globalization and modernization in Bali. Keywords: Contractual Marriage, Shift in Legal Culture, Land Rights of Foreign Nationals